Utility of Winter Wheat According to Visual and Microbiological Fusarium Infection, as Well as Toxin Examination - Veres, Edina; Borbély, Mária (Acta Agraria Debreceniensis, 2003)
In 1998 the Fusarium infection was studied visually and microbiologically and also F-2, T-2, HT-2, DAS and DON contamination were measured using 22 winter wheat samples. The correlation between the different parameters of 22 wheat samples were determined by regression analysis. According to our results we can state the following. There is no significant connection between the results of visual, microbiological and toxicological examinations. This means that no certain conclusion can be drawn about the toxin contamination of samples – which is a determining factor of its utility – based on the visual symptoms and the plate dilution method. Our results indicate however – though it is not proven statistically – that those samples in which the Fusarium infection did not exceed the limit of the standard, also had low toxin contamination, therefore they can be used as components of forage. It is a considerable problem, however, that according to the visual qualification, such samples are excluded from the later utilisation, wherein the toxin contamination does not justify such action. Therefore, it is necessary to examine the toxin content of those samples which show high infection by visual symptoms. To reducing the number of expensive toxin examinations it would be advisable to change the currently used 0,5% limit which is indicated in the standard for a higher value of infection, for example to 2%, as recommended by Mesterházy (1998).